Penggunaan Premises and Conclusions Gapped terhadap Makna “Memukul Dengan Rotan” Berdasarkan Amsal 23:14 - Sualang, Farel Yosua; Butin, Mariam Van; Sumarmi, Ni Putu (Sekolah Tinggi Teologi Jaffray Jakarta, 2023)
Collections of Book Proverbs provide many thematic teachings such as: wealth, poverty, and parental upbringing to children. Much emphasis is also placed on teaching parents to children in collections of Proverbs, especially Proverbs 23:14. Proverbs 23:14 is widely used as a basis for teaching parents to children, especially in the meaning of the phrase